2019
DOI: 10.1007/s10879-019-09417-8
|View full text |Cite
|
Sign up to set email alerts
|

Constructions of Nonagency in the Clients’ Initial Problem Formulations at the Outset of Psychotherapy

Abstract: This multiple case study investigated how clients construct nonagentic positions when formulating their problems in the beginning of their first psychotherapy session. The initial problem formulations of nine clients entering psychotherapy were analyzed with a detailed model drawing on discursive methodology, the 10 Discursive Tools model (10DT). We found ten problem formulation categories, each one distinguished by the tool from the 10DT model primarily used to construct nonagency. All clients gave several pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…All participants narrated about problems they don't have a grip on (C1). This first category shows parallels with established literature on client agency, suggesting that clients present themselves as lacking agency at the outset of therapy (Toivonen et al, 2020;Wahlström, 2006). On the one hand, participants presented themselves as lacking agency by attributing their problems to general, external circumstances and the malevolence of specific others, as such situating the locus of control outside themselves (Rotter, 1966).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…All participants narrated about problems they don't have a grip on (C1). This first category shows parallels with established literature on client agency, suggesting that clients present themselves as lacking agency at the outset of therapy (Toivonen et al, 2020;Wahlström, 2006). On the one hand, participants presented themselves as lacking agency by attributing their problems to general, external circumstances and the malevolence of specific others, as such situating the locus of control outside themselves (Rotter, 1966).…”
Section: Discussionsupporting
confidence: 61%
“…Thus, agency is considered as a central theme in narratives and is related to improved mental health. Yet, research up until now mostly approaches agency in a quantitative manner (e.g., Adler et al, 2008 ; Adler, 2012 ; Hobbs & Mclaren, 2009 ; Irving, 2004 ) or with a focus on how nonagency is discursively constructed at the outset of and throughout treatment (e.g., Seilonen and Wahlström, 2016 ; Toivonen, Kurri and Wahlström, 2020 ). In spite of the extensive evidence for agency as both a precursor of good therapy outcome as well as a crucial aspect during the therapy process, little research can be found on the nature of agency in clients’ narratives.…”
mentioning
confidence: 99%
“…Presenting agency problems at the onset of therapy is common in patients (Toivonen et al, 2019(Toivonen et al, , 2020, and thus regaining a sense of agency has been identified as a crucial focus in psychotherapy practice (e.g., Lilliengren and Werbart, 2010;Levitt et al, 2016;Wahlström and Seilonen, 2016). When analyzing patient narratives over the course of therapy, a stable increase in agency was found across patient characteristics (e.g., demographics, personality traits), and in various conditions (e.g., Kristmannsdottir et al, 2019).…”
Section: Continuity With Prior Empirical Researchmentioning
confidence: 99%
“…Recent language-based orientations explore how patients position themselves with respect to their problems and construct a sense of agency and reflectivity in interaction with the therapist (Avdi, 2012; Avdi et al, 2015; Leiman, 2012; Seilonen & Wahlström, 2016; Toivonen et al, 2019, 2020). In investigating agency as a discursive phenomenon, they distance themselves from content-based and quantitative approaches to the agency that conceptualize it in terms of self-mastery (e.g., Adler, 2012; Adler et al, 2008; McAdams, 2002).…”
Section: Agency’s Coming-into-beingmentioning
confidence: 99%
“…In investigating agency as a discursive phenomenon, they distance themselves from content-based and quantitative approaches to the agency that conceptualize it in terms of self-mastery (e.g., Adler, 2012; Adler et al, 2008; McAdams, 2002). The research group of Wahlström, for instance, shows how the expression of nonagency at the onset of therapy is in itself already an agentic act (Wahlström, 2006) and how the construction of nonagency potentially fluctuates with every dialogical turn (Toivonen et al, 2020).…”
Section: Agency’s Coming-into-beingmentioning
confidence: 99%